PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN SCIENTIFIC INQUIRY BERBASIS PICTORIAL RIDDLE PADA MATERI POKOK CAHAYA - ALFRISKA SILALAHI (LP2MTBM MAKARIOZ, 2019)
The scientific inquiry learning model is one of the student centered learning models. This model brings students to investigate an issue, identify problems, and encourage them to solve those problems. This research was conducted at the junior high school level in Light Material in 2 classes selected by cluster random sampling technique, namely the experimental class and the control class to see the effect of this learning model on student learning outcomes. The average value of the experimental class pretest was 31.53 and the control class obtained an average pretest value of 30.81. After treatment in each class, the average value of posttest in the class with pictorial riddle based scientific inquiry learning was 76.39 while students who were taught using conventional learning were 69.86. Likewise with the observations of student learning activities observed in the application of pictorial riddle-based scientific inquiry learning has increased.